(3TQM CSeGA GdCOhjIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3QH Sgd hJee gPG TQM eG hbY ef CSeGA GdCOhjI HGdjhfGfjI , hjHOC HMQa GdCda HeG GSeg CHGfS , hgh GdCHfhS HGdjhfGfjI s
(3BNQgG (B:s
(3eGOI XdGe , hgj YTjI fGaYI , hGddg hdi Pdc hgh Gdehab hGdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3CMQa GdChQGb ef CYdi eJCcdgs
(3GfXQg eY (B" (3eGdG jSY GdWHjH Lgdg (B" (3Qbe (B" 70-703"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B128 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs